Systematic Literature Review: Variasi Bahasa pada Remaja dalam Penggunaan Media Sosial - Anni Kholilah Siregar; Fauziah Nasution; Shoni Faried Sopiyanto; Nahda Sahriani Lubis (EduPsyCouns: Journal of Education, Psychology and Counseling, 2022)
Abstract: Along with the development of the times, social media is used as a medium of communication for intermediaries in conveying information. This makes the Indonesian language also develop following language trends on social media. Language is also created with the peculiarities of each group and adapted to the culture of that group. The specificity of language creates a variety or variety of languages that are used and understood by a particular group of people. One of the language variations used on social media, especially by teenagers, is slang. The purpose of this research is to conduct a literature review system regarding language variations in adolescents in the use of social media. The research method used is a Systematic Literature Review using three journal articles that are appropriate to the research topic. The conclusion obtained is that there are six patterns of the formation of language variations in adolescents on social media, namely in the form of abbreviations, acronyms, shortening of words, words that are made up, and words that experience a shift in meaning. In addition, the variations of slang used by teenagers on social media can also be divided into two based on the meaning of the language in it, namely slang that has a positive meaning and slang which has a negative meaning. Abstrak: Seiring dengan berkembangnya zaman, media sosial digunakan sebagai media komunikasi untuk perantara dalam menyampaikan informasi. Hal ini membuat bahasa Indonesia juga berkembang mengikuti tren bahasa di media sosial. Bahasa juga tercipta dengan kekhasan setiap kelompok dan disesuaikan dengan kebudayaan kelompok tersebut. Kekhasan bahasa menciptakan ragam atau variasi bahasa yang dipakai dan dipahami oleh suatu kelompok masyarakat tertentu. Salah satu variasi bahasa yang digunakan di sosial media terutama oleh para remaja adalah bahasa gaul. Tujuan dari penelitian ini adalah untuk melakukan system literature review mengenai variasi bahasa pada remaja dalam penggunaan media sosial. Metode penelitian yang digunakan ialah Systematic Literature Review dengan menggunakan tiga artikel jurnal yang sesuai dengan topik penelitian. Kesimpulan yang didapatkan yaitu terdapat enam pola pembentukan variasi bahasa pada remaja di sosial media yaitu berupa singkatan, akronim, pemendekan kata, kata yang dipelesetkan, dan kata yang mengalami pergeseran makna. Selain itu variasi bahasa gaul yang digunakan remaja di media sosial juga dapat dibedakan menjadi dua berdasarkan makna bahasa yang ada didalamnya, yaitu bahasa gaul yang memiliki makna positif dan bahasa gaul yang memiliki makna negatif.